Modeling road building, deforestation and carbon emissions due deforestation in the Ecuadorian Amazon: the potential impact of oil frontier growth. Issue 6 (2nd November 2017) - Mena, Carlos F.; Laso, Francisco; Martinez, Patricia; Sampedro, Carolina
ABSTRACT: In the Ecuadorian Amazon roads play the major role in transforming land cover. Since the beginning of the oil development in this region, oil exploration and road building have been linked. The objectives of this paper are twofold: First, to present a scenario of future deforestation as result of expanding the oil frontier in the Ecuadorian Amazon until the year 2030. Second, to produce an analysis of possible carbon emission scenarios as results of the deforestation produced. This paper tries to shed light into how the development of new oil concessions impact land associated environmental services. The paper uses spatial explicit simulations, that are based on parameters built using past land transitions from areas that experimented oil development, and that explain possible outcomes in the year 2030 using current and predicted road network. Simulations indicate that under current transition probabilities and a conservative scenario road construction, more than 2 million hectares will be affected, which is 35% of the area covered by concessions, which would release 51 to 148 MT of carbon to the atmosphere. This paper illustrates the strong links between road building and deforestation, where even small amount of road construction can have large effects on land cover.